Thermal Hazard Study on the Synthesis of 3-Amino-4-nitrofurazan - Liping Chen; Jiayu Lyu; Juan Zhou; Meiling Liu; Zichao Guo; Wanghua Chen (Chemical Engineering Transactions)
The synthesis of 3-amino-4-nitrofurazan (ANF), a critical precursor for various monofurazan derivatives, involves the oxidation of 3,4-diaminofurazan (DAF) using an oxidizing system of CH3SO3H-H2O2-Na2WO4. This complex process produces two primary outcomes: the desired product ANF and a by-product, 3,3'-diamino-4,4'-azofuroxide (DAOAF). To evaluate the thermal hazards associated with this reaction, reaction calorimetry (RC1) was utilized to study the thermal behavior, followed by separation, washing, extraction, evaporation, and drying of the final reaction mixture, resulting in two solid products: a filter cake and the dried filtrate. The yields of ANF and DAOAF were quantified through HPLC analysis. Kinetic parameters were derived using a five-step reaction model based on heat generation rate data. Findings indicate that the fourth reaction step, responsible for ANF formation, demonstrated the highest heat release at 599.9 kJ·mol-1 with an activation energy of 93.0 kJ·mol -1. The Maximum Temperature of Synthesis Reaction (MTSR) was established at 55°C, while adiabatic calorimetry suggested limited thermal stability, with a TD24 of 23°C. Consequently, Dr. Stoessel’s thermal runaway classification was expanded from five to six classes to assess the thermal risks better, categorizing the oxidation reaction as Class 6.